KENABIAN DINAMIS ATAU FINAL - Armyn Hasibuan (IAIN Padangsidimpuan, 2019)
This paper is a literature review that contains dynamic or final prophethood.Â Prophethood is a very interesting thing to talk about. Through this paper, it is expected that readers will be easier to understand about the concept of prophethood is dynamic or final. In this paper it has been found through the evidence of the argument that it is clear that prophethood was final through the explanation of the Koran. Then, this paper does not need a continuation to be explored by future researchers.